NOOGENETIC NEUROSIS, NOODYNAMIC PROCESSES AND SELF-REFLECTION PERSONALITY IN EXISTENTIAL ANALYSIS AND LOGOTHERAPY - Shcherbakova, Anastasiya (The Journal of V. N. Karazin Kharkiv National University, Series Philosophy. Philosophical Peripeteias, 2024)
The article studies the concept of noogenetic neurosis and noodynamics in Victor Frankl's existential analisys. The aim of the article is structural analysis of the aforementioned concepts with an account of methodological and therapeutic tasks of logotherapy and existential analysis. It reviews the authentic peculiarities of the logotherapeutic method and existential analysis considering the background of the first and the second Vienna schools of psychoanalysis and studies the principal distinctions in interpretation of the "drive" term. The analysis of the existential motivation theory in the context of existential frustration and the will to meaning is performed. The four fundamental motivational questions in their relation to existential frustration, noogenic neurosis, and healthy processes of sense creation are reviewed. The complex nature of the noogenetic neurosis is reviewed in relation to possible scenarios of existential vacuum state flow. It is reviewed on the following levels: psychic, somatic, and noetic. The purpose and the character of the noetic dimension concept are reviewed within the structural model of the psyche from existential analysis. The article also reviews the notion of categorical values and their structural place in motivation shaping and sense creation. The nature of interaction between categorical values and fundamental motivations is studied. In addition, the conceptual reconstruction of the ontological status of being-in-the-world is conducted in the context of self-transcendence.